Perbandingan Kejadian Inflamasi dan Rekurensi antara Benang Nylon dan Benang Vicryl Pasca Operasi Pterigium dengan Teknik Limbal-Conjunctival Autograft di RSUD dr. Soedarso Pontianak - ., Affannul Hakim (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Inflammation and recurrency are the most common complications after pterygium surgery. Recently, various methodes have been tried to reduce the incidence of both complications. Objective: The objective of this study was to compare the incidence of inflammation and reccurency after pterygium surgery with nylon and vicryl suture using limbal-conjunctival autograft technique in RSUD dr. Soedarso Pontianak. Methods: This was an observational analytic study with cross sectional design. Data were obtained using medical records from patients operated from January 2011 until December 2012 by consecutive sampling method. Minimal sample estimation was 30 subject (CI=90%). Data were analyzed by Chi Square test, Fisher test is used as the alternative test. Result: The incidence of inflammation was higher in the vicryl group (43%) than nylon group (23%). Chi Square test: p=0,024. The incidence of recurrency was higher in the vicryl group (9%) than nylon group (3%). Fisher test: p=0,603. Conclusion: There was a significant comparison between type of suture with the incidence of post-operative inflammation. There was no comparison between type of suture with the incidence of recurrency. Keywords : Nylon, Vicryl, Pterygium Surgery, Limbal-conjunctival autograft, Post Surgical Inflammation, Pterygium Recurrency. 1) Medical school, Faculty of Medicine, Tanjungpura University, Pontianak, West Kalimantan. 2) Departement of ophtalmology disease, Regional General Hospital dr. Soedarso, Pontianak, West Kalimantan. 3) Department of physiology, Faculty of Medicine, Tanjungpura University, Pontianak, West Kalimantan.